0713 Longitudinal Sleep Position Patterns and Breathing Parameters in Pregnancy. (25th May 2022) - Katz, Juliana; Sanapo, Laura; Dunsiger, Shira; Guillen, Melissa; Avalos, Ashanti; Aldana, Annaly; Wilson, Danielle; Bourjeily, Ghada
Abstract: Introduction: Supine sleep position during pregnancy has been linked to increased risk of stillbirth in retrospective studies. However, existing literature is largely cross-sectional and limited by recall bias and self-reporting of sleep position. This study aims to use objectively-measured sleep position to quantify sleep position change between trimesters and its influence on maternal respiratory health. Methods: This study is a secondary analysis of data from a study investigating maternal sleep, among women with singleton pregnancies and overweight or obesity. Each participant underwent level III sleep apnea monitoring using Noxturnal T3 devices (Nox Medical, Georgia, US), in the first (0-12 weeks) and third (29-40 weeks) trimester of pregnancy. Using accelerometry, the software differentiated 5 positions including supine, right lateral, left lateral, prone, and upright. The studies were scored using AASM 2012 recommended criteria. The first non-upright position was recorded as going-to-bed position. The number of sleep position changes was calculated using only positions that lasted ≥30 seconds. Results: A total of 126 women were included. Mean BMI was 34.00±5.14 and mean age was 30.46±5.40 years. Mean number of position changes was similar in early (14.19±7.82) vs. late (14.58±8.25) pregnancy. There was a significant correlation between sleep onset position and predominant sleep position in both early (p=0.001) and late (p<0.01) pregnancy. However, supine going-to-bed position predicted predominant supine sleep in only 47% of women. There was a significant change in sleep position between early and late pregnancy (p=0.04) with a reduction in supine sleep (51.6% to 30.2%) and an increase in left lateral sleep (24.6% to 37.3%). Only in the third trimester, there was a significant positive correlation between time spent supine and oxygen desaturation index (r=0.22, p=0.01), and a trend toward positive correlation with respiratory event index (r=0.15, p=0.08). Conclusion: Going-to-bed position predicts predominant sleep position in less than half of women with overweight and obesity. Time spent supine in late pregnancy correlates with measures of sleep-disordered breathing. More prospective studies are needed to evaluate the potential for sleep position changes over time as a potentially modifiable risk factor for maternal and neonatal health outcomes. Support (If Any): R01HL130702, R01HD078515, SRA grant